Bentonite as an Adsorption Surface for Bromothymol Blue Dye from Aqueous Solution - Kawther Ahmed Sadiq (Journal of Global Pharma Technology, 2016)
Accomplishment of Adsorption of dye from aqueous solution on the surface of bentonite was done under the following optimized conditions: temperature, initial concentration, contact time and weight surface. Via utilizing the technique of UV-Vis spectophotometry at (λmax= 432 nm) the quantitative estimation of the dye adsorption has been performed. this study has demonstrated that the more increasing of  adsorption with the more increasing of temperature from 25 ˚C to 45 ˚C also increasing of clay weight (0.1-1.1 g).calculating thermodynamic parameters like change in the free energy (∆G), the enthalpy (∆H), the entropy (∆S). Results of adsorption isotherms obtained in this study were inconsitence with fitted with Freund lich adsorption isotherm.Keywords: Adsorption, Bentonite, Bromothymol blue.